Chitosan as A Silver (Ag) Adsorbent on Hospital Photography Fixer Waste - Fernanda, Decky Danuarta; Rupiasih, Ni Nyoman; Wendri, Nyoman; Eri Sandriani, Ni Wayan (BULETIN FISIKA; Vol 20 No 1 (2019): BULETIN FISIKA, 2019)
Abstrak – A research on the use of chitosan as an adsorbent of silver (Ag) on the photography fixer waste from hospital has been carried out. Chitosan used was in the form of powder and membrane. Chitosan powder used was 0.5 g, 1 g, 2 g and 5 g, and the membrane used was a 2% chitosan membrane of 5 g. The adsorbent materials added to 50 mL of fixer waste and soaked for 24 hours. The Whatmann filter paper was also used by filtering method. The results showed that the 2% chitosan membrane of 5 g gave the highest silver adsorption percentage of 95.99%. The percentage of adsorption by chitosan powder of 0.5, 1, 2 and 5 g were 4.41%, 6.43%, 7.82% and 36.42% respectively. While the percentage of silver adsorption by Whatman filter paper was 0.05%. The used of chitosan in the form of membrane is the most effective adsorbent of silver on photographic fixer wastes.